Análise do tempo de utilização por viscosimetria de argamassas colantes - Bellei, Poliana (2016)
The Brazilian standard NBR 14081-1 (ABNT, 2012), establishes parameters for the open time test, tensile bond strength and slip resistance for adhesive mortars. However, the standards for wall and floor tiling (NBR 13755 and NBR 13754) establish 2h30min as the limit time for the adhesive mortar application. Thus, to avoid detachment of the ceramic tiles through time, an analysis of the rheological behavior of the adhesive mortars is necessary. This research evaluates the rheology of adhesive mortars types AC-I, AC-II and AC-III by viscosity parameters in the times of 30, 180 to 300 minutes, which directly influences the slip resistance and bond strength of the ceramic tiles. In some cases, the test method was able to determine the time of consolidation of adhesive mortars, indicating difference in viscosity in the course of time. Most mortars showed a tendency at the times from 30 to 180 minutes, but beyond that, at 300 minutes their performance characteristics changed. This may cause problems in the settlement stages of ceramic tiles and later in its performance and durability.